Effects of Piston motion on the power generated by Stirling cycle machines - hazmy, Majed (Journal of King Abdulaziz University: Engineering Sciences, 2022)
This paper uses a simple model to estimate the power output of Stirling engine when giving the pistons a continuous motion with a prescribed pattern, fixed frequency, and a variable phase shift for different operational temperature ratios. Two continuous motions patterns, sinusoidal and modified sinusoidal, have been examined against the discontinuous motion of the ideal cycle. The power produced from engines having continuously moving pistons is lower than the power produced from the ideal cycle. The power ratio decreases as the temperature ratio increases. the highest produced power with a temperature ratio of 1.5, is 97% of the ideal cycle and it occurs at a phase-shift of 81o. Operating at ±10o off the highest power phase shift condition reduces the output power by 5-7%. For modified sinusoidal motion, the highest output power is 88% when the phase shift is 55o. Operating at ±10o off the maximum power phase shift condition reduces the output power by 2%. Moreover, at the highest output phase shift condition, the power output ratio drops from 97% to 93%, for sinusoidal motion as the cycle temperature ratio changes from 1.5 to 3. For modified sinusoidal motion, the output power drops from 88% to 78% at the highest phase shift condition.